Pengaruh Content Marketing dan E-WOM Terhadap Keputusan Pembelian pada C offee Shop Galdina Kopi dengan Brand Awareness sebagai Variabel Intervening - Gisela Maslakhatul Umah; Syariefful Ikhwan; Azizah Indriyani (CV. Ulil Albab Corp, 2024)
This study aims to find out how content marketing and E-WOM affect the Purchase Decision of Galdina Kopi Coffee Shop with Brand Awareness and Buying Interest as Intervening Variables. This study uses a type of quantitative descriptive research using AMOS 22 Structural Equation Modelling (SEM) analysis. The population used in this study is catering customers with a total of 220 respondents. The results of the study show that content marketing has a positive effect on brand awareness with a CR value of 9,372 (CR ≥ 1.96) and a probability value of 0.000 (p ≤ 0.05). Content marketing has no positive effect on purchase decisions with a CR value of 0.438 (CR ≥ 1.96) and a probability value of 0.661 (p ≤ 0.05). Electronic word of mouth (E-WOM) has a positive effect on buying miat with a CR value of 8,150 (CR ≥ 1.96) and a probability value of 0.000 (p ≤ 0.05). Electronic word of mouth (E-WOM) has a positive effect on buying miat with a CR value of 8,150 (CR ≥ 1.96) and a probability value of 0.000 (p ≤ 0.05). Electronic word of mouth (E-WOM) has no positive effect on purchase decisions with a CR value of 0.840 (CR ≥ 1.96) and a probability value of 0.401 (p ≤ 0.05). Brand awareness has a positive effect on purchase decisions with a CR value of 3,666 (CR ≥ 1.96) and a probability value of 0.000 (p ≤ 0.05). Buying interest had no positive effect on the purchase decision with a CR value of 1.186 (CR ≥ 1.96) and a probability value of 0.236 (p ≤ 0.05).